THE PERCEPTIONS OF EMPLOYEES ON ENVIRONMENTAL MANAGEMENT DIMENSIONS: A STUDY AT TWO STATES IN THE SOUTHERN ZONE OF MALAYSIA - Siron R.B.; Kasavan S. (Malaysian Institute Of Planners, 2024)
In recent years, many companies had to make their supply chains more sustainable by focusing not only on economic goals but also on environmental goals. Employee involvement is critical to the successful implementation of environmental management dimensions in the workplace. This study aims to determine employees' perceptions of the environmental management dimensions employed for a district council in the Southern zone state of Malaysia. Using a questionnaire, data were collected from 50 respondents (16 companies/facilities) in the Johor state and 32 respondents (17 companies/facilities) in the Malacca state. The main findings show that more than half of the respondents understood environmental management and were willing to consider environmental practices in their organisation/facility. This study also verifies the environmental issues that need to be considered in environmental management implementation. Relevant recommendations are then provided to facilitate an understanding of where the attention should be directed in developing and improving environmental management in organisations. 2023 by MIP.